Correct management and low rate of contagiousness of healthcare workers in a University Hospital in Southern Italy: from contact tracing to serological investigation - Squeri, Raffaele; Levita, Antonio; Intelisano, Rosanna; Costa, Gaetano Bruno; Mancuso, Giuseppe; Grasso, Loredana; D'Amato, Smeralda; Mazzitelli, Francesco; Squeri, Andrea; Midiri, Angelina; Biondo, Carmelo; Alesci, Domenica; et al. (Acta Biomedica Atenei Parmensis, 2020)
The COVID-19 epidemic, which began in Wuhan in December 2019, quickly spread all over the world, leading in a few months to a high number of deaths also in healthcare workers. The purpose of the study is to a) describe the importance of a correct management of SARS-CoV-2 infections; b) report the number of positive healthcare workers after the epidemic phase and to describe their socio-characteristics data, the main methods of transmission and the symptoms; c) to report the seroconversion rate of healthcare workers  (HCWs). The study was conducted from March 9, 2020 to June 19, 2020 in three phases:1) in a first phase, we implemented the guidelines to be followed for patient care in our hospital; 2) in a second phase, we provided the epidemiological investigation/contact tracing of HCWs; 3)  we collected swabs on all healthcare workers and we also performed serological investigation. The number of healthcare workers under surveillance is of 2611 subjects and, of these, only 0.65% contracted COVID-19. In particular, 70.6% of these have been infected in the healthcare setting, 11, 8% in the family and 17.6% returning from high risk areas. Ultimately, only 0.1% of HCWs dedicated to the treatment of COVID-19 patients contracted the infection (one was asymptomatic). Only 2% of HCWS were positive for serological investigation.